Mastering ROS for robotics programming : design, build, and simulate complex robots using Robot Operating System and master its out-of-the-box functionalities /: design, build, and simulate complex robots using Robot Operating System and master its out-of-the-box functionalities. (2018) - Joseph, Lentin
No abstract available